(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
As many as 90% of CRF patients choose Hemodialysis (HD) therapy to maintain their lives. HD treatment is closely related to the patient’s quality of life. Family is the closest figure in providing care for CRF patients. The results showed that the family support has impact to increasing the quality of life. This is in the form of attitudes, actions, family acceptance of patients, motivational and encouraging, and providing help with sincerity. Empowerment to the families of CRF patients is carried out through education and psychological assistance. This is intended to provide a clearer understanding that the needs of CRF patients with HD are in a hypersensitive state from all aspects. Their condition of despairing is the main cause of their struggle to do self-care. Intense and optimal social support from the family brings hope and a positive attitude to CRF patients. This encourages patient confidence to recover by doing optimal self-care such as maintaining diet, resting patterns, good stress management, maintain health control routine, exercising and routinely undergoing HD therapy. Patients will happy to follow this routine because they feel meaningful to their family and others.